Physical Activity and Renal Transplantation - Vincenzo Bellizzi; Adamasco Cupisti; Alessandro Capitanini; Patrizia Calella; Claudia D'Alessandro (Karger Publishers, 2014)
Renal transplantation is burdened by high cardiovascular risk because of increased prevalence of traditional and disease-specific cardiovascular risk factors and, consequently, patients are affected by greater morbidity and mortality. In renal transplanted patients, healthy lifestyle and physical activity are recommended to improve overall morbidity and cardiovascular outcomes. According to METs (Metabolic Equivalent Task; i.e. the amount of energy consumed while sitting at rest), physical activities are classified as sedentary (<3.0 METs), of moderate-(3.0 to 5.9 METs) or vigorous-intensity (≥6.0 METs). Guidelines suggest for patients with chronic kidney disease an amount of physical activity of at least 30 minutes of moderate-intensity activity five times per week (min 450 MET-minutes/week). Data on physical activity in renal transplanted patients, however, are limited and have been mainly obtained by mean of non-objective methods. Available data suggest that physical activity is low either at the start or during renal transplantation and this may be associated with poor patient and graft outcomes. Therefore, in renal transplanted patients more data on physical activity obtained with objective, accelerometer-based methods are needed. In the meanwhile, physical activity have to be considered as an essential part of the medical care for renal transplanted recipients.